Understanding Slow Learner Student Development: Strategy Implications and Learning Effectiveness - Mauzifa; Lulu Nur Lathiifah Jamiilah; Subhi Amali; Ahmad Shabri; Uus Ruswandi (al-Afkar, Journal For Islamic Studies, 2025)
This article describes the development of slow learner students, especially for an educator to be able to adjust effective learning strategies in achieving optimal learning goals. The research approach used in formulating the objectives is qualitative using the literature study method. The mechanism of collecting data from various sources of literature that can be accounted for, such as books, articles, similar research, skrispi, thesis, and other official websites. The findings that researchers found from the various data collected are then described as follows: 1. Recognizing the development of slow learner students is an important aspect that must be mastered by an educator to ensure inclusive teaching. 2. Slow learner students have unique characteristics that are influenced by biological, environmental, and psychological factors. 3. Effective learning includes differentiation, repetition of material, and adjustment of evaluation as needed. 4. Good collaboration between teachers, parents and schools is needed to create a supportive learning environment, both academically and social-emotionally, so that the learning potential of slow learner students can develop to the fullest.